Relación entre nivel de conocimiento y prácticas en Alimentación saludable en madres con niños menores de cinco Años del caserío Bello Horizonte Junio – Septiembre 2014 - Bustamante Julca, Fanny Milagros (2014)
This study aimed to determine the degree of knowledge and practice healthy eating Mothers with children under five years of the village of Bello Horizonte, in the period June-September 2014. A quantitative, descriptive, correlational study was carried out in Cross section. The sample consisted of 30 mothers with children under 5 glass of milk Members of that community which met the inclusion and exclusion criteria. To measure The variables knowledge and healthy eating practices in the survey was used as method Further observation. The results are: 77.3% of mothers with children over five years, have a medium level of Knowledge on healthy eating; 83.3% of mothers with children under five years in the Village of Bello Horizonte have unfavorable practices about healthy eating; the usual Feeding mothers with children under five years in the hamlet Bello is based breads, rice, Banana, milk, oil, sugar, cassava and potatoes; that consumption of fish and beef is with A frequency of 1-2 times per month; and consumption of fruits and vegetables with a Frequency of weekly or biweekly. Concluding: There is no statistically significant Relationship between the level of knowledge and healthy eating practices among Mothers with children under five years in the hamlet Bello Horizonte (p = 0.336> 0.05).